On the FIR emission from intracluster dust - Popescu, Cristina C.; Tuffs, Richard J.; Fischera, Jörg; Völk, Heinrich J. (Astronomy and astrophysics, 2000)
We make predictions for the diffuse far-infrared (FIR) emission from dust in the intracluster medium (ICM) of the Virgo cluster using detailed information on potential dust sources, grain heating and sputtering rates available for this cluster from recent optical and X-ray studies. In the cluster core we identify the winds of red giant and supergiant IC stars as the main continuous sources of IC grains, with a dust injection rate of 0.17 Msunyr-1. The predicted FIR surface brightness from this dust component is however a factor of ~ 10 below the detection limit of currently available - telescopes. Grains that are impulsively removed from spiral galaxies by ram-pressure stripping as they enter the cluster core region can sporadically dominate the grain injection rate into the ICM. However, these events should lead to the appearance of rare, relatively bright, localised FIR sources around the parent galaxy. The outer regions of dynamically young clusters like the Virgo cluster have a further potential source of intracluster grains since they are still accreting freshly infalling spiral galaxies which are presumably contained in an accreting intergalactic medium (IGM). We show that cosmics ray driven winds from the infalling spirals can inject grains into a subvirial IGM that is external to the observed X-ray-emitting ICM. Sputtering during the injection process and in the IGM is weak, so that the injected grains should accumulate in the IGM until the infall brings them into contact with the hot ICM. Normalising the mass loss rate in the galactic winds to the mass-loss rate and B-band luminosity of the Milky Way, we estimate a dust accretion rate of 1.0 Msunyr-1 from the infalling IGM. This effect dominates the dust injection rate from known sources embedded in the hot Virgo ICM. Thus, any detection of diffuse IR emission would probe the current dust accretion rate for the cluster, acting as an indicator of the youth and the dynamical state of the cluster. The predictions for the Virgo cluster are generalised to other clusters and the possibility of detection of dynamically young clusters at cosmological distances is discussed. Although dominated by the discrete source emission from galactic disks, it is possible that diffuse sub-mm dust emission from the ICM could be detected in - experiments similar to those designed to map the sub-mm excess due to the Sunyaev-Zeldovich effect in distant clusters.
Gesehen am 08.12.2020